U.S. DOE NETL methodology for estimating the prospective CO2 storage resource of shales at the national and regional scale. (August 2016) - Levine, Jonathan S.; Fukai, Isis; Soeder, Daniel J.; Bromhal, Grant; Dilmore, Robert M.; Guthrie, George D.; Rodosta, Traci; Sanguinito, Sean; Frailey, Scott; Gorecki, Charles; Peck, Wesley; Goodman, Angela L.
Graphical abstract: Highlights: The majority of shales will act as seals, but shales that have been hydraulically fractured may serve as CCS reservoirs. US-DOE-NETL method for carbon dioxide storage resource estimation in shale formations. Intended for national-scale prospective resource estimation and screening. Abstract: While the majority of shale formations will serve as reservoir seals for stored anthropogenic carbon dioxide (CO2 ), hydrocarbon-bearing shale formations may be potential geologic sinks after depletion through primary production. Here we present the United States-Department of Energy-National Energy Technology Laboratory (US-DOE-NETL) methodology for screening-level assessment of prospective CO2 storage resources in shale using a volumetric equation. Volumetric resource estimates are produced from the bulk volume, porosity, and sorptivity of the shale and storage efficiency factors based on formation-scale properties and petrophysical limitations on fluid transport. Prospective shale formations require: (1) prior hydrocarbon production using horizontal drilling and stimulation via staged, high-volume hydraulic fracturing, (2) depths sufficient to maintain CO2 in a supercritical state, generally >800 m, and (3) an overlying seal. The US-DOE-NETL methodology accounts for storage of CO2 in shale as a free fluid phase within fractures and matrix pores and as an sorbed phase on organic matter and clays. Uncertainties include but are not limited to poorly-constrained geologic variability in formation thickness, porosity, existing fluid content, organic richness, and mineralogy. Knowledge of how these parameters may be linked to depositional environments, facies, and diagenetic history of the shale will improve the understanding of pore-to-reservoir scale behavior, and provide improved estimates of prospective CO2 storage.